FHL2 activates β-catenin/Wnt signaling by complexing with APC and TRIM63 in lung adenocarcinoma - Jian Gao; Yong-Qiang Ao; Jie Deng; Miao Lin; Shuai Wang; Jia-Hao Jiang; Jian-Yong Ding (Translational Oncology)
Objectives: Four and a half LIM domain 2 protein (FHL2) was reported to regulate the progression of various cancers and this study aimed to clarify the intrinsic mechanism of FHL2 facilitating the progression of lung adenocarcinoma. Methods: In this study, bioinformatic analysis and immunohistochemistry staining were used to confirm the FHL2 levels in patients with lung adenocarcinoma. The potential influence of FHL2 on the biological function of lung adenocarcinoma cells was verified in vitro and in vivo. To uncover the potential mechanism contributing to the advance of lung adenocarcinoma, liquid chromatography‒mass spectrometry and immunoprecipitation assays were performed to detect the partners of FHL2. Results: FHL2 levels were upregulated in lung adenocarcinoma and contributed to a dismal prognosis. Moreover, in vitro and in vivo assays suggested that genetic inhibition of FHL2 undermined the viability, migration and invasion of lung adenocarcinoma cells, while forced expression of FHL2 showed the opposite trend. Mechanistically, liquid chromatography‒mass spectrometry and coimmunoprecipitation assays revealed that FHL2 could function as a scaffold to enhance TRIM63-mediated ubiquitination of APC. The degradation of APC further stabilized β-catenin and activated Wnt signaling pathway. Conclusion: Collectively, this study uncovered the underlying mechanism by which FHL2 regulates the biological characteristics of tumors and provided a novel target for lung adenocarcinoma treatment.